2017
DOI: 10.1088/1361-6587/aa5c02
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of intense ultrashort laser pulses with cryogenic He planar jets

Abstract: We study the interaction of intense ultrashort laser pulses with cryogenic He jets using 2d/3v relativistic Particle-in-Cell simulations (XOOPIC). Of particular interest are laser intensities (10 15 − 10 20 ) W/cm 2 , pulse lengths ≤ 100 fs, and the frequency regime ∼ 800 nm for which the jets are initially transparent and subsequently not homogeneously ionized. Pulses ≥ 10 16 W/cm 2 are found to drive ionization along the jet and outside the laser spot, the ionization-front propagates along the jet at a fract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Accordingly, EUV radiation can propagate into the plasma volume, in contrast to optical radiation in the visible or near-infrared spectrum which launches density waves. 19 With an absorption length of 9 µm for the 13.5 nm EUV radiation in our experiments, the EUV pulses are sufficiently absorbed and isochorically heat the cryogenic hydrogen target by photo ionization. We have recently shown that microscopic plasma properties can be investigated by EUV scattering: the elastic scattering cross section increases by more than a factor of two when solid density hydrogen dissociates and becomes ionized as a result of electron-ion heat transfer.…”
Section: Introductionmentioning
confidence: 97%
“…Accordingly, EUV radiation can propagate into the plasma volume, in contrast to optical radiation in the visible or near-infrared spectrum which launches density waves. 19 With an absorption length of 9 µm for the 13.5 nm EUV radiation in our experiments, the EUV pulses are sufficiently absorbed and isochorically heat the cryogenic hydrogen target by photo ionization. We have recently shown that microscopic plasma properties can be investigated by EUV scattering: the elastic scattering cross section increases by more than a factor of two when solid density hydrogen dissociates and becomes ionized as a result of electron-ion heat transfer.…”
Section: Introductionmentioning
confidence: 97%
“…The density and temperature profiles throughout the target are usually inhomogeneous. The resulting compression factor, degree of ionization, and temperature are dependent on the intensity and length of the laser pulse, its shape, and spot size . XRTS is then used to probe the WHDM state.…”
Section: Introductionmentioning
confidence: 99%